2013
DOI: 10.7205/milmed-d-12-00454
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Tourniquets Exposed to the Afghanistan Combat Environment Stored in Individual First Aid Kits Versus on the Exterior of Plate Carriers

Abstract: Between February and May 2010, 1st Battalion, 6th Marines reported a 10% (10/92) breakage rate for tourniquets. One theory suggested was that tourniquets were weakened by exposure to the Afghan environment. Our study was designed to compare three groups of Afghanistan-exposed tourniquets to unexposed tourniquets. The three experimental arms were: (1) Afghan-exposed tourniquets worn on the plate carrier, (2) Afghan-exposed tourniquets carried in the Individual First Aid Kit (IFAK) and wrapped in manufacturer pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…[11,13] The use of a personal first aid kit also increases the effectiveness of established tourniquets. [18] There is no doubt that despite disadvantages of tourniquet use, tourniquets greatly increase the chances of survival of victims. [10,17,18,19] The use of tourniquets is not exclusively reserved for military institutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,13] The use of a personal first aid kit also increases the effectiveness of established tourniquets. [18] There is no doubt that despite disadvantages of tourniquet use, tourniquets greatly increase the chances of survival of victims. [10,17,18,19] The use of tourniquets is not exclusively reserved for military institutions.…”
Section: Discussionmentioning
confidence: 99%
“…[18] There is no doubt that despite disadvantages of tourniquet use, tourniquets greatly increase the chances of survival of victims. [10,17,18,19] The use of tourniquets is not exclusively reserved for military institutions. Because of the easy and quick access to specialist care, in case of massive hemorrhage in case of civil casualties, assistance is provided in stages, the last of which is the tourniquet application.…”
Section: Discussionmentioning
confidence: 99%
“…The mean sample size of included studies was 55.60 (SD = 130.39, Mdn = 20, IQR = 26) participants; with a mean of 210.91 applications (SD = 304.03, Mdn = 102, IQR = 152). Study sample sizes ranged from 1 participant (Kragh et al, 2019) to 773 participants (Weppner et al, 2013), and total tourniquet applications ranging from 20 individual applications (Peponis et al, 2016) to 1,546 individual applications (Weppner et al, 2013) (Table 1).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Device failures included mechanical teeth skipping ; windlass, strap or baseplate failure (Beaven et al, 2021) biological, radiological or nuclear (CBRN, or extensive device deformation (Slaven et al, 2015)50, 75, 100, 125, 150, 175 (CAT only. Failure rates were not compared because some devices were used extensively (Slaven et al, 2015) 50, 75, 100, 125, 150, 175 (CAT only, exposed to environmental degradation (Childers et al, 2011;Weppner et al, 2013)1st Battalion, 6th Marines reported a 10% (10/92, and while both of these conditions significantly increased the likelihood of failure, they were not consistently reported in the literature.…”
Section: Advantage (Degree Of Mechanical Advantage)mentioning
confidence: 99%
“…Historically, haemorrhage from extremity injuries account for a significant percentage of preventable trauma deaths (1). The primary function of a tourniquet is to stop life-threatening and uncontrolled external haemorrhage.…”
Section: Introductionmentioning
confidence: 99%